The role of sexual compulsivity in unprotected intercourse among STI patients in Shanghai, China - Yang Ni; Hengan Liu; Ruijie Gong; Mei Shi; Shuxian Zhang; Suping Wang; Yong Cai (BMC, 2021)
Abstract Background Sexual compulsivity (SC) and its relationship with unprotected intercourse (UI) have long been an intriguing topic, but its existential meaning in the management of public health or, more precisely, sexually transmitted infections (STIs) has rarely been studied to date. This study examines whether SC plays a role in UI among sexually active STI patients. Method A cross-sectional study was conducted in two sexual transmitted disease (STD) clinicals of Shanghai Skin Diseases Hospital in Shanghai. Totally 664 sexually active STI patients were included. Results The ages of the 664 participants ranged from 18 to 76 years, with 58.73% between 26 and 40 years old. 449 (191 male and 258 female) reported had UI during the past 6 months. Although the only statistically significant difference (p < 0.01) was in relation to UI with a casual sexual partner, the difference between male/female and regular/casual sexual partners remained evident. Conclusions SC is evidently a potential predictor of UI with a casual sexual partner in male STI patients, while the use of condoms is more likely to be affected by other factors. In addition to general sexual education, counseling interventions should be provided by health institutions, and specific intervention methods targeting gender and sexual partners should be considered.